Influence of temperature and glass composition on aluminum nitride contact angle; IOP Conference Series: Materials Science and Engineering; Vol. 156 : Materials and Technologies of New Generations in Modern Materials Science - Tarnovskiy R. (2016, 2016)
Title screen